Effects of holding and reheating time using microwave on microbial load of ready-to-eat foods in selected restaurants in Selangor, Malaysia - Hersi, Mohamed Aden (2018)
Due to changes in the lifestyle of societies, the demand of ready to eat (RTE) food is on the increase worldwide. In Malaysia urbanization has affected how and where people get their foods. Eating out has become part of the Malaysian culture and hence the need to examine the quality of RTE foods served at local restaurants. The aim of this study was to assess the effect of holding and the microwave reheating times on the microbial content of RTE foods prepared and served at local restaurants. A total of 120 samples were analyzed to evaluate the effect of holding time and on the microbial content of the food samples. Four samples of each food type from every restaurant were microbiologically tested for Coliforms and Escherichia coli bacteria. Another set of samples, 120 samples from the same restaurants were collected to estimate the effect of varying microwave reheating time on the microbial content of the food. However, this time, samples were analyzed after being subjected to different levels of microwave time; namely, 0 seconds, 30 seconds, 45 seconds and 60 seconds. Out of the collected samples, which were, Plain Rice (PR), Roti Canai (RC), Fried Chicken (FC), Chicken Fried Rice (CFR), Fried Noodles (FN), and Nasi Lemak (NL); FN had the highest microbial content of both Coliform contents ranging from 3.6 to over 1100 MPN/g. Nonetheless, although there was an increase in the number of microorganisms in the samples tested, holding time had no significant effect on the microbial content of any of the samples tested, except for FN and NL where the holding time significantly affected the microbial load. The effect of the microwave time on microbial load was a statistically significant one. This was observed in the TPC content of all the samples except for RC, PR, and NL which had the lowest microbial content. There was no statistically significant difference between different microwave times of 30, 45 and 60 seconds. In conclusion, all the level of microwave time significantly affected the microbial content of ready to eat foods while the specified storage time didn’t significantly affect the microbial content of the ready to eat foods. Restaurants varied in their compliance with the international standards tested against them. Nevertheless, most of the Samples collected were compliant with the satisfactory classification of the Hong Kong (HK), New South Wales, Australia (NSW) and International Commission on Microbiological Specifications for Foods (ICMSF) standards for the microbial content of ready to eat foods.